InSe Tribotronic Transistors: Low‐Voltage Operational, Low‐Power Consuming, and High Sensitive Tactile Switch Based on 2D Layered InSe Tribotronics (Adv. Funct. Mater. 19/2019). (7th May 2019) - Li, Mengjiao; Yang, Feng‐Shou; Hsiao, Yung‐Chi; Lin, Che‐Yi; Wu, Hsing‐Mei; Yang, Shih‐Hsien; Li, Hao‐Ruei; Lien, Chen‐Hsin; Ho, Ching‐Hwa; Liu, Heng‐Jui; Li, Wenwu; Lin, Yen‐Fu; et al.
Abstract : Tribotronics is believed to be a promising technology to drive electronics by external stimulation. In article number 1809119, Wenwu Li, Yen‐Fu Lin, Ying‐Chih Lai, and co‐workers demonstrate a low‐voltage operational, integratable, powering saving, and high sensitivity tactile sensor based on a InSe tribotronic transistor. The ultrahigh on/off current modulation and extraordinarily low operation voltage of the 2D‐layered user‐interactive system set new records for smart tribotronics, which could benefit the progress of 2D material devices for potential applications in smart interfaces.